80-110-GHz Broadband Linear PA With 33% Peak PAE and Comparison of Stacked Common Base and Common Emitter PA in InP - Liu, Zheng; Sharma, Tushar; Sengupta, Kaushik (IEEE microwave and wireless components letters, 2021)
This work presents a high efficiency, compact 80-110-GHz InP power amplifier (PA) based on stacked common base (CB) topology and a counterpart design using conventional stacked common emitter (CE) topology. The comparison between the two exhibits that the former delivers higher power gain, superior-gain compression behavior (linearity), and higher back-off efficiency in W -band in 250-nm InP heterojunction bipolar transistor (HBT). At 90 GHz, the stacked CB/CE PA achieves 11.8 dB/6dB gain, 33%/34% peak PAE, 16.8%/14.5% PAE at 6-dB back-off, and Psat of 18.7 dBm/19.6 dBm. Modulation test exhibits an EVM of 2.38% at 11.8-dBm average power supporting 3 Gbps 64-QAM for the stacked CB PA. The stacked CB PA with 17.9-18.9-dBm Psat across 80-110 GHz demonstrates one of the highest efficiency, broadband and linear PAs in W -band using InP technology.